A Modified Technique of Konno Aortoventriculoplasty for Redo Aortic Valve Replacement Procedures - Bobylev, Dmitry; Breymann, Thomas; Ono, Masamichi (The Thoracic and Cardiovascular Surgeon, 2014)
This article puts forward a modified technique of Konno aortoventriculoplasty for repeat procedures. After incision of the ventricular septum, this approach involves aortic valve replacement using a mechanical valved conduit, reimplantation of the coronary arteries, and graft replacement of the ascending aorta. This modification allows the removal of the diseased ascending aortic wall caused by a previous patch enlargement or poststenotic dilation.
Keywords: Konno aortoventriculoplasty; congenital subaortic stenosis; mechanical valved conduit